The incorrect use of CD75 as a synonym for ST6GAL1 has fostered the expansion of commercial "ST6GAL1" antibodies that do not recognize ST6GAL1. (5th July 2022) - Haldar, Barnita; Hwang, Jihye; Narimatsu, Yoshiki; Clausen, Henrik; Bellis, Susan L
Abstract: The ST6GAL1 Golgi sialyltransferase is upregulated in many human malignancies, however, detection of ST6GAL1 protein in cancer tissues has been hindered by the prior lack of antibodies. Recently, numerous commercial antibodies for ST6GAL1 have become available, however, many of these do not, in fact, recognize ST6GAL1. Decades ago, the CD75 cell-surface epitope was mistakenly suggested to be the same molecule as ST6GAL1. While this was rapidly disproven, the use of CD75 as a synonym for ST6GAL1 has persisted, particularly by companies selling "ST6GAL1" antibodies. CD75 is reportedly a sialylated epitope which appears to encompass a range of glycan structures and glycan carriers. In this study, we evaluated the LN1 and ZB55 monoclonal antibodies, which are advertised as ST6GAL1 antibodies but were initially developed as CD75-recognizing antibodies (neither was raised against ST6GAL1 as the immunogen). Importantly, the LN1 and ZB55 antibodies have been widely used by investigators, as well as the Human Protein Atlas database, to characterize ST6GAL1 expression. Herein, we used cell and mouse models with controlled expression of ST6GAL1 to compare LN1 and ZB55 with an extensively validated polyclonal antibody to ST6GAL1. We find that LN1 and ZB55 do not recognize ST6GAL1, and furthermore, these 2 antibodies recognize different targets. Additionally, we utilized the well-validated ST6GAL1 antibody to determine that ST6GAL1 is overexpressed in bladder cancer, a finding that contradicts prior studies which employed LN1 to suggest ST6GAL1 is downregulated in bladder cancer. Collectively, our studies underscore the need for careful validation of antibodies purported to recognize ST6GAL1.